PLANNING OF HUMAN RESOURCE COMPETENCY DEVELOPMENT IN PT.XYZ WITH TAGUCHI METHOD - Mariza K; Diah Wilis Lestarining Basuki (Widyagama University of Malang, 2018)
The problem of human resources is still a concern within the company to remain competitive in this globalization world. This shows that the problem of human resources greatly affect the implementation and success of the company in achieving goals and objectives. The company demand to obtain the development process and get quality human resources more urgent. And the development of human resource competence is necessary. This study uses experimental testing with several parameters of validity and reliability testing. For testing analysis using Taguchi Method. Based on the Response Table for Signal to Noise Ratios Nominal is best obtained taguchi test results obtained values obtained from the effect plot for means with the approach of table of means, then the intellectual competence is needed for the improvement of HR performance. Keywords: HR, Competence, Taguchi Method